A new hybrid photovoltaic/thermal and liquid desiccant system for trigeneration application. (15th September 2018) - Su, Bosheng; Han, Wei; Qu, Wanjun; Liu, Changchun; Jin, Hongguang
Highlights: A new solar-powered CCHP based on photovoltaic/thermal technologies is proposed. A two-stage liquid desiccant cycle is integrated to use the heat from PV/T collector. Two conditions of whether to use excess heat from the PV/T collector are compared. Comparative analysis shows the new system has an advanced integrated performance. Abstract: Conventional combined cooling, heating and power (CCHP) systems based on fossil fuels, with an acceptable energy performance, however, intensify the greenhouse effect worldwide. Using solar energy in distributed energy systems has the potential to further reduce fossil fuels consumption, and ease carbon emissions. This paper proposes a novel CCHP system by combining concentrated photovoltaic/thermal (PV/T) technology with an advanced air-handling process that realizes independent control of temperature and humidity. The heat produced from a PV/T collector is for desiccant regeneration in a two-stage liquid desiccant cycle in summer, and can be directly supplied to nearby users in winter. An office building under typical climate conditions of Beijing in 2002 was adopted to determine its various energy demands. Due to the efficient use of solar energy, annual energy saving ratio and CO2 emissions reduction ratio are predicted to be 73.28% and 74.55%, respectively. Two extreme conditions determining whether the excess heat from the PV/T collector is used were compared to demonstrate the top and bottom limitations of economic performance. The integrated performance, considering energy, environment and economic factors, reaches 37.48% when no excess heat from PV/T collector is used, and it can be further improved by thermal storage or recovering the excess heat to produce other products. This study provides a new solar utilization technology for trigeneration with advanced integrated performance.